MANAJEMEN KEBIJAKAN SUBSIDI LIQUEFIED PETROLEUM GAS (LPG) TABUNG 3 KG DI KECAMATAN BAJENG BARAT KABUPATEN GOWA - Hamzah, Alief Munandar; Nasrulhaq, Nasrulhaq; Riskasari, Riskasari (Universitas Muhammadiyah Makassar, 2022)
This study aimed to determine the management of the Liquefied Petroleum Gas (LPG) subsidy policy in Bajeng Barat District, Gowa Regency. The method used in this research is descriptive qualitative with case study approach. Data were collected through interviews, observation, and documentation. Furthermore, the data is processed and analyzed qualitatively with systematic stages. The results show that the LPG subsidy policy management has been implemented well in several management functions. However, the implementation of other management functions is still not optimal. Planning is carried out in accordance with the authority of each party. The organization does not take place formally because each party has different duties and responsibilities. The briefing is carried out by the Gowa Regency Government seriously through the relevant regional apparatus organizations, but agents and bases are always not orderly in reporting realization data to the government. Coordination is carried out actively if there are problems such as tube scarcity and substandard distribution. Control or supervision is sometimes less than optimal due to limited government personnel.Keywords: Management, Subsidy Policy, LPG